Morphological and anatomical features of Bauhinia vahlii Wight & Arnott. grown in Egypt - Ahmed Hassan Elbanna, Engy Abdel-hamid Mahrous, Amal El-Sayed Khaleel, Taha Shahat El-alfy (Journal of Applied Pharmaceutical Science, 2016)
Leaves and stems of plants of genus Bauhinia, family Fabaceae subfamily Caesalpinoideae, have been used as folk remedies for treatment of numerous health problems mainly diabetes. The genus is famous for the characteristic camel’s foot shape of its leaves and bearing flowers ranging from white, yellow to purple. The shape and size of both flower and leaf are essential for species characterization. This study targets the morphological and histological profiling of Bauhinia vahlii Wight & Arnott. due to its recently evidenced biological importance. Morphologically, B. vahlii can be distinguished by being a huge evergreen climber with numerous pairs of coiled revolute tendrils. Its branches bear numerous large bilobed hairy leaves and white flowers that turns buff by time. The flowers show three long fertile stamens and two short staminodes. The commonly used parts, leaves and stems, were subjected to a deeper investigation. Microscopically, they are characterized by long non-glandular hairs with three small basal cells and an elongated distal one and that are rare in Caesalpinoideae. B. vahlli was recently segregated into a separate genus; Phanera based on the presence of tendrils, nature of its flower’s androceum and phylogenetic data.
Keywords: Bauhinia vahlii, Phanera vahlii, leaf, stem, macromorphology, micromorphology, hair.